Access to fracture risk assessment by FRAX and linked National Osteoporosis Guideline Group (NOGG) guidance in the UK—an analysis of anonymous website activity. Issue 1 (January 2017) - McCloskey, E.; Johansson, H.; Harvey, N.; Compston, J.; Kanis, J.
Abstract Summary In the UK, fracture risk guidance is provided by the National Osteoporosis Guideline Group (NOGG). NOGG usage showed widespread access through direct web-based linkage to FRAX. The facilitated interaction between fracture risk assessment and clinical guidelines could usefully be adopted in other countries. Introduction In the UK, guidance on assessment of osteoporosis and fracture risk is provided by the National Osteoporosis Guideline Group (www.shef.ac.uk/NOGG ). We wished to determine access to this guidance by exploring website activity. Methods We undertook an analysis of FRAX and NOGG website usage for the year between 1st July 2013 and 30th June 2014 using Google Analytics software. Results During this period, there was a total of 1, 774, 812 sessions (a user interaction with the website) on the FRAX website with 348, 964 of these from UK-based users; 253, 530 sessions were recorded on the NOGG website. Of the latter, two-thirds were returning visitors, with the vast majority (208, 766; 82 %) arising from sites within the UK. The remainder of sessions were from other countries demonstrating that some users of FRAX in other countries make use of the NOGG guidance. Of the UK-sourced sessions, the majority was from England, but the session rate (adjusted for population) was the highest for Scotland. Almost all (95.7 %) of the UK sessions arose from calculations being passed through from the FRAX tool (www.shef.ac.uk/FRAX ) to the NOGG website, comprising FRAX calculations in patients without a bone mineral density (BMD) measurement (74.5 %) or FRAX calculations with a BMD result (21.2 %). National Health Service (NHS) sites were identified as the major source of visits to the NOGG website, comprising 79.9 % of the identifiable visiting locations, but this is an underestimate as many sites from within the NHS are not classified as such. Conclusion The study shows that the facilitated interaction between web-based fracture risk assessment and clinical guidelines is widely used in the UK. The approach could usefully be adopted in other countries for which a FRAX model is available.